1992
DOI: 10.1007/bf02637689
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of hydrolysis ofNigella sativa (black cumin) seed oil catalyzed by native lipase in ground seed

Abstract: Kinetics of the lipolysis ofNigella sativa oil catalyzed by native lipase in crushed seed were studied between 20 and 90°C. Data fitted the pseudo first‐order rate equation at 20, 30 and 40°C; and the pseudo second‐order equation at 50, 60 and 70°C, but neither equation fit at 80 and 90°C. Lipolysis approximated first‐order with respect to water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…This leads to greater potential for lipolytic activity during extraction which in turn can increase the AV. This justification came in accordance with a previous study (Dandik and Aksoy, 1992) although the authors estimated Peak areas are means of three injections ± SD. the effect of temperature on lipase activity by subjecting the seeds to different temperatures in an oven instead of proceeding under real mechanical pressing conditions which generate inherent heat, as the case in our investigation.…”
Section: Discussionsupporting
confidence: 90%
“…This leads to greater potential for lipolytic activity during extraction which in turn can increase the AV. This justification came in accordance with a previous study (Dandik and Aksoy, 1992) although the authors estimated Peak areas are means of three injections ± SD. the effect of temperature on lipase activity by subjecting the seeds to different temperatures in an oven instead of proceeding under real mechanical pressing conditions which generate inherent heat, as the case in our investigation.…”
Section: Discussionsupporting
confidence: 90%
“…One can cite the different studies that were carried out with the lipase from black cumin (Nigella sativa L). Similarly to the castor bean lipase, the Nigella sativa L. lipase is also active in dormant seeds [21]. It was shown that this lipase was an efficient catalyst for many reactions in both the crude and the immobilised form.…”
Section: Potential Applications Of Plant Lipasesmentioning
confidence: 98%
“…Ustun et al, 1990;Dandik and Aksoy, 1992;Abdel-Aal and Attia, 1993;Nergiz and Otles, 1993;Dandik and Aksoy, 1996;El-Dhaw and Abdel-Munaem, 1996;Takruri and Damed, 1998;Ustun et al, 1998;Abu Jadayil, 1999;Ali and Blunden, 2003;Atta, 2003;Nickavar et al, 2003;Ramadan and Mörsel, 2003;Ramadan and Mörsel, 2004;Al-Saleh et al, 2006;Ashraf et al, 2006;Cheikh-Rouhou et al, 2007. Their finding also suggests that it contains 49.8-50.7% of PUFA, 25.0-26.6% of MUFA while saturated fatty acids only account for 22.7-25.5% of the total oil contents. According to their findings, linoleic, oleic, and palmitic acids were found to be in higher quantities (Nickavar et al, 2003;Ashraf et al, 2006).…”
Section: Introductionmentioning
confidence: 98%